Eco-Theological Pedagogy for Sustainable Character Formation in Islamic Elementary Education - Fikri Alfina Zahro; Mukni'ah Mukni'ah; Dyah Nawangsari; Syaiful Rizal (Departemen Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2026)
Environmental degradation has intensified the need for Islamic elementary education to foster students' sustainable character through spiritually grounded environmental learning. However, the integration of Islamic eco-theological values into classroom pedagogy, school culture, and daily ecological habituation remains underexplored. This study examines the implementation of eco-theological pedagogy at SD Darus Sholah Jember, Indonesia. Using a qualitative case study design, data were collected through observations, semi-structured interviews, and document analysis involving 22 participants, including the principal, teachers, students, parents, and an environmental program coordinator. The data were analysed through data condensation, data display, and conclusion drawing. The findings reveal that eco-theological pedagogy operates through five interconnected dimensions: Islamic eco-theological values, reflective Islamic learning, teacher exemplarity, ecological habituation, and collaborative school culture. These dimensions transform environmental education from a rule-based cleanliness program into a spiritually meaningful and habit-forming process. Students developed eco-spiritual consciousness, environmental responsibility, discipline, cooperation, and emerging ecological habits through Qur'anic reflection, water-saving practices, waste sorting, plant care, and parent-school collaboration. Nevertheless, inconsistent environmental behavior outside school, limited facilities, and uneven family-community support remain key challenges. This study contributes to Islamic sustainability education by proposing eco-theological pedagogy as an integrative framework for linking faith, ecological ethics, pedagogical practice, and sustainable character formation in Islamic elementary schools.